DEVELOPMENT TRENDS OF THE CONCEPT OF “HUMAN CAPITAL” AS A UNIT OF QUALITATIVE CHARACTERISTICS AND RESOURCE CAPABILITIES OF PERSONNEL - TELNOV Anatolіі (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In wartime conditions, Ukraine has observed trends in the loss of human capital associated with forced migration, the death of military personnel, etc. In such difficult times, it is human capital that determines the possibility of Ukraine’s existence as a competitive state. Therefore, modern scientific research is paying increasing attention to the topic of human capital at different levels of the economic system. Analysis of the epistemology of the concept of "human capital" will contribute to the development of new approaches, the formation of prospects for its development. Thus, the study of approaches to the development of the theory of human capital will allow us to determine the directions of further development of human capital, its restoration and formation in the prevailing conditions. Ukraine has significant reserves in terms of restoring human capital. Therefore, in this context, the problem of identifying modern tendencies and trends in approaches to the formation of qualitative components of human capital, outlining key characteristics that contribute to the acquisition of competitive advantages is relevant in the context of the need to restore the human capital of Ukraine. The purpose of the article is to generalize approaches to interpreting the essence of the concept of "human capital" that have developed in modern economic science, to substantiate the role and importance of human capital for gaining competitive advantages, and to determine the main trends in the development of this concept taking into account modern conditions. The article substantiates the role and importance of human capital for strengthening competitive positions, summarizes the views of modern scientists on the meaning of the concept of "human capital". The main trends in the formation of scientists’ views on the interpretation of the meaning of the concept of "human capital" are identified. The definition of the concept of "human capital" is formulated taking into account the identified trends. Approaches to the restoration of human capital are proposed.